Improving the Ecological Tax Reform in Germany - Model Based Analysis of the Ecological and Economic Impacts of Alternative Proposals - Bernd Meyer; Christian Lutz (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2002)
In 1999 the red/green administration in Germany induced an ecological tax reform, which burdens energy consumption and uses the tax revenue to reduce social security distributions. As in other countries the design of the taxation does not follow textbook considerations, but is marked by many restrictions and exemptions coming out of the political bargaining process. The tax rates are dynamic until 2003. The further development of the ecological tax reform is subject of an intensive discussion. The paper at hand compares the ecological and economic impacts of the status quo with those of different proposals to change the structure of the taxation and presents the instrument of the analysis - the model PA)TA RHEI. This 58-sector econometric inputoutput-model for Germany fully integrates an energy system for 29 energy carriers, a traffic- model, a land- use- model, as well as an S)A- model, which depicts the redistribution of income between enterprises, households, the government and the rest of the world and calculates the budget constraints of these institutions. PA)TA RHEI is part of the global I)FORUM system of models.
Keywords: D50; H22; 330; Ecological Tax Reform; Germany; Ecological and Economic Impacts; Alternative Proposals